Correlation of Cesarean Section and Curettage History with Placenta Previa at Limboto Regional Hospital - Amanda Auliya Ayuwa; Fadil Hidayat (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2025)
Objective: To investigate the correlation of cesarean section and curettage history with placenta previa at Dr. M.M. Dunda Limboto Hospital.Methods: A cross-sectional analytical study was conducted from January to February 2025, involving 180 pregnant women with gestational age ≥28 weeks from records from 2022-2024. Data were collected through consecutive sampling from medical records. Chi-square analysis was performed using SPSS version 24.Result: Among women with a history of cesarean section, 8.3% (12/145) had placenta previa compared to 54.3% (19/35) without such a history (p<0.001; PR=0.152, 95% CI: 0.082-0.284). Similarly, only 2.9% (1/35) with a history of curettage had placenta previa compared to 20.7% (30/145) without a curettage history (p=0.012; PR=0.138, 95% CI: 0.019-0.978). These findings suggest apparent protective effects that contradict established literature.Conclusion: Although statistically significant associations were observed between surgical histories and placenta previa in unexpected directions, these probably reflect study artifacts rather than actual protective effects. Multivariate analysis will be crucial in future research to account for confounding variables.Hubungan Riwayat Sectio Caesarea dan Kuretase dengan Plasenta Previa di RSUD LimbotoAbstrak Tujuan: Penelitian ini bertujuan menganalisis hubungan antara riwayat kuretase dan sectio caesarea dengan kejadian plasenta previa di RSUD Dr. M.M. Dunda Limboto.Metode: Penelitian analitik potong lintang dilakukan pada Januari – Februari 2025, melibatkan 180 ibu hamil dengan usia kehamilan ≥28 minggu dari rekam medis 2022 – 2024. Data dikumpulkan melalui consecutive sampling. Analisis Chi-square dilakukan menggunakan SPSS ver 24. : Pada kelompok dengan riwayat sectio caesarea, 8,3% (12/145) mengalami plasenta previa dibandingkan 54,3% (19/35) tanpa riwayat tersebut (p<0,001; PR=0,152, 95% CI: 0,082-0,284). Demikian pula, hanya 2,9% (1/35) dengan riwayat kuretase mengalami plasenta previa dibandingkan 20,7% (30/145) tanpa riwayat kuretase (p=0,012; PR=0,138, 95% CI: 0,019-0,978). Temuan ini menunjukkan efek protektif yang bertentangan dengan literatur medis.Kesimpulan: Meskipun ditemukan asosiasi signifikan antara riwayat bedah dan plasenta previa dalam arah yang tidak terduga, temuan ini kemungkinan merupakan artefak penelitian daripada efek protektif sejati. Analisis multivariat sangat penting untuk penelitian masa depan guna mengontrol faktor perancu.Kata kunci: kuretase; plasenta previa; sectio caesarea.